MOTIVASI BELAJAR SEBAGAI DETERMINAN PRESTASI BELAJAR DALAM PEMBELAJARAN DARING DENGAN MENGGUNAKAN E- LEARNING - Amelia Fahruniza; Riswan Jaenudin; Dwi Hasmidyani (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2021)
This research aims to determine the effect of learning motivation on student achievement using e-learning applications. The research method is ex-post facto with a quantitative approach. The population and sample in this study were all students of the Economic Education Study Program, FKIP Sriwijaya University, in the 2018 Academic Year as many as 73 students. Data collection techniques using a questionnaire and using a modified Likert scale. The data analysis technique used is descriptive quantitative analysis and documentation. The hypothesis test used is the Pearson Product Moment correlation and the t test results show that learning motivation has a positive influence on learning achievement. Therefore, student learning achievement can be improved through increasing student motivation